Process Innovation: Enabling Change by Technology Basic Principles and Methodology: A Management Manual and Textbook with Exercises and Review Questions - Schallmo, Daniel R. A. (Springer Berlin Heidelberg : Gabler, 2018)
This management manual and textbook introduces the theoretical basics of process management and provides a procedural model for process innovation. The procedural model makes it possible to develop customer-oriented processes in a structured manner and to design them in order to meet changing requirements. This textbook has been recommended and developed for university courses in Germany, Austria and Switzerland. This book enables readers to understand and apply the seven phase procedural model for process innovation in order to design and implement innovative processes. Exercises and review questions test understanding of the theoretically acquired knowledge. Content - Theoretical Basics - Existing Approaches - Procedural Model for Process Innovation - Techniques for Analyzing the Business Model - Techniques for Planning the Process Architecture - Techniques for Developing the Process Vision - Techniques for Developing the Process Deliverables - Techniques for Planning the Process Flow - Techniques for Creating the Process Management - Techniques for Implementing Process Innovation The authors Prof. Dr. Daniel R.A. Schallmo is an economist, management consultant, lecturer, and author. He is a professor at the Ulm University of Applied Science and is director of the Private Institute for Business Model Innovation. Prof. Dr. Leo Brecht is the Chairman of the Institute of Technology and Process Management at the University of Ulm and Titular Professor at the University of St. Gallen, Switzerland. Bujar Ramosaj (M. Sc.) is a research assistant at the Institute of Technology and Process Management at the University of Ulm.